2016
DOI: 10.21276/sjams.2016.4.6.64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on consumption of anesthetic agents, duration of surgery, time to extubation and post-operative emergence during endoscopic nasal surgeries: a pilot study

Abstract: Our aim was to study the effects of dexmedetomidine on anesthetic consumption, duration of surgery, time to extubation and post-operative emergence when used as an adjunct to general anesthesia in endoscopic nasal surgeries. Fifty two patients scheduled for elective nasal surgery (Functional Endoscopic Sinus Surgery and Functional Endoscopic Nasal surgery) were randomized into two groups. Dexmedetomidine-group (D) and placebo or control-group (C). Dexmedetomidine was administered to the D group at a bolus dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Nevertheless, using a high dose of inhaled anesthetics is associated with hepatic or renal injury and a prolonged recovery from anesthesia leading to delayed patient discharge. 9 Recently, dexmedetomidine was identified to attenuate stress-induced hemodynamic responses and produce relatively stable hemodynamics throughout the surgery. Bhagat et al and Gupta et al reported that the intraoperative consumption of fentanyl and isoflurane was significantly less in the dexmedetomidine group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, using a high dose of inhaled anesthetics is associated with hepatic or renal injury and a prolonged recovery from anesthesia leading to delayed patient discharge. 9 Recently, dexmedetomidine was identified to attenuate stress-induced hemodynamic responses and produce relatively stable hemodynamics throughout the surgery. Bhagat et al and Gupta et al reported that the intraoperative consumption of fentanyl and isoflurane was significantly less in the dexmedetomidine group.…”
Section: Discussionmentioning
confidence: 99%
“…An increased amount of inhaled anesthetics can also be administrated to decrease blood pressure. Nevertheless, using a high dose of inhaled anesthetics is associated with hepatic or renal injury and a prolonged recovery from anesthesia leading to delayed patient discharge 9 . Recently, dexmedetomidine was identified to attenuate stress‐induced hemodynamic responses and produce relatively stable hemodynamics throughout the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This derivative of fentanyl reduces blood pressure by triggering the release of histamine and centrally deactivating vasoconstriction [ 22 ]. In comparison to other opioids, it enhances hemodynamic stability and maintains cerebral blood flow during demanding surgical procedures [ 23 ]. Remifentanil administered via patient-controlled analgesia has shown inhibitory effects on apoptotic pathways and oxidative stress, thereby providing organ protection and reducing inflammatory responses [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the included studies were extracted using standardized forms and independently examined by the two authors. The evaluated outcomes consisted of operative time [1,3,6,, mean intraoperative bleeding [1,6,9,[12][13][14][15]17,22,[25][26][27]33,34,36,37], dose of intraoperative fentanyl administered [1,6,13,15,19,22,30,32,38], postoperative pain [3,7,10,11,22,33,36,39], the occurrence of postoperative nausea and vomiting (incidence or percentage of patients) [3,7,10,11,13,19,22,27,29,31,33,39,40], and intraoperative hypotension…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%